Experimental Study on the Performance of a Countercurrent Dew-point Indirect Evaporative Cooler - Chu Junjie; Huang Xiang; Sun Tiezhu; Geng Zhichao; Zhang Hong; He Huaming (Zhileng xuebao, 2019)
A new countercurrent dew-point indirect evaporative cooler was developed, and its cooling performance was experimentally studied in this work. The wet-bulb efficiency, dew-point efficiency, and cooling capacity of the cooler were tested and analyzed under various working conditions simulating dry area, moderate-humidity area, and high-humidity area in an enthalpy-difference laboratory. The experimental results show that the wet-bulb efficiency reached 105.6% and the dew-point efficiency reached 76% under standard drying conditions (dry-bulb temperature 38 ℃ and wet-bulb temperature 23 ℃) and air-flow ratio of secondary air/primary air = 1.1. The cooling capacity was tested as 2.83 kW, and the dry-bulb temperature decrease of the cooler reached 15.2 ℃. By the experimental results simulating the working conditions of Urumqi and standard dry environment, the dew-point indirect evaporative cooling technology shows many advantages and broad application prospects in the hot and dry areas in northwestern China.